Gratifikasi Seksual Sebagai Bentuk Perluasan Tindak Pidana Korupsi Menurut Hukum Positif di Indonesia - Dwi Seno Wijanarko (Jurnal Kajian Ilmu Kepolisian dan Anti Korupsi, 2024)
Currently there is a category of sexual gratification that has received a lot of attention from the public and law enforcement officials. This sexual gratification is different from the gratification that we know in general. The difference lies in the object. Sexual gratification is a form of ensuring women's dignity. Therefore, this research will discuss the regulation of sexual gratification based on positive law in Indonesia and its evidence. From the results of the analysis, it is known that sexual gratification can be included in the provisions of Article 12 B paragraph 1 of Law 20 of 2001 concerning Amendments to Law Number 31 of 1999 concerning the Eradication of Corruption Crimes. This can be found in the phrase "other facilities" where "facilities" themselves are defined as the means used to facilitate an implementation. Therefore, the use of sexual service facilities with the aim of achieving any desire is the intention of the gratifier. Proving sexual gratification in eradicating corruption in Indonesia is based on criminal procedural law. Referring to the Criminal Procedure Code (KUHAP) in Article 184 paragraph (1) and Article 26A of Law Number 20 of 2001 Jo. Law Number 31 of 1999 uses a reverse or balanced evidence system where the burden is on both the Public Prosecutor and the defendant to prove the crime of sexual gratification for which the defendant is charged.